Surviving crack: a qualitative study of the strategies and tactics developed by Brazilian users to deal with the risks associated with the drug - Nappo Solange A; Sanchez Zila M; Ribeiro Luciana A (BMC, 2010)
Abstract Background Due to marginalization, trafficking violence, conflicts with the police and organic and social psychological problems associated with the drug, crack is one of the most devastating drugs currently in use. However, there is evidence that some users manage to stay alive and active while using crack cocaine for many years, despite the numerous adversities and risks involved with this behavior. In this context, the aim of the present study was to identify the strategies and tactics developed by crack users to deal with the risks associated with the culture of use by examining the survival strategies employed by long-term users. Method A qualitative research method was used involving semi-structured, in-depth interviews. Twenty-eight crack users fulfilling a pre-defined enrollment criterion were interviewed. This criterion was defined as the long-term use of crack (i.e., at least four years). The sample was selected using information provided by key informants and distributed across eight different supply chains. The interviews were literally transcribed and analyzed via content analysis techniques using NVivo-8 software. Results There was diversity in the sample with regard to economic and education levels. The average duration of crack use was 11.5 years. Respondents believed that the greatest risks of crack dependence were related to the drug's psychological effects (e.g., cravings and transient paranoid symptoms) and those arising from its illegality (e.g., clashes with the police and trafficking). Protection strategies focused on the control of the psychological effects, primarily through the consumption of alcohol and marijuana. To address the illegality of the drug, strategies were developed to deal with dealers and the police; these strategies were considered crucial for survival. Conclusions The strategies developed by the respondents focused on trying to protect themselves. They proved generally effective, though they involved risks of triggering additional problems (e.g., other dependencies) in the long term.